Teaching the disadvantaged - Houston Independent School District, TX.; Houston Independent School District, TX. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Guidelines for teaching and understanding the disadvantaged child are presented in this report. Specifically discussed are the psychological and physical characteristics of the disadvantaged child, motivation and reinforcement technIQues, and technIQues for instructing pupils in language arts, social science, science, and mathematics. The duties of various members of the school's supportive staff are also described. (lb)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Ancillary School Services; Disadvantaged Youth; Health; Individual Characteristics; Language Arts; Mathematics Instruction; Parent Teacher Conferences; Psychological Characteristics; Reading Materials; Reinforcement; Science Education; Self Concept; Social Studies; Staff Role; Student Motivation; Teaching Methods